2019
DOI: 10.3390/en12081448
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation of a Novel Low-Cost Photovoltaic Panel Active Cooling System

Abstract: Renewable energy sources are the most useful way to generate clean energy and guide the transition toward green power generation and a low-carbon economy. Among renewables, the best alternative to electricity generation from fossil fuels is solar energy because it is the most abundant and does not release pollutants during conversion processes. Despite the photovoltaic (PV) module ability to produce electricity in an eco-friendly way, PV cells are extremely sensitive to temperature increments. This can result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 42 publications
1
17
0
3
Order By: Relevance
“…Water spraying is a type of active cooling technique that is used solar-powered pumps and is sprayed on the PV panels. Based on the scientific evaluations, the water spraying angles (90 o , 180 o , 360 o ) are tested; the best angle to spray water is the nozzle model at 90o, since best for water consumption and film water uniformly on the surface of PV module [66]. By using this technique, the temperature is decreased up to 35 0 c. Further, the research was carried out to improve the PV solar module electrical efficiency, and the study result attested that the electrical efficiency was enhanced by 15% in extreme environmental weather conditions [41].…”
Section: Water Spraying Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Water spraying is a type of active cooling technique that is used solar-powered pumps and is sprayed on the PV panels. Based on the scientific evaluations, the water spraying angles (90 o , 180 o , 360 o ) are tested; the best angle to spray water is the nozzle model at 90o, since best for water consumption and film water uniformly on the surface of PV module [66]. By using this technique, the temperature is decreased up to 35 0 c. Further, the research was carried out to improve the PV solar module electrical efficiency, and the study result attested that the electrical efficiency was enhanced by 15% in extreme environmental weather conditions [41].…”
Section: Water Spraying Techniquementioning
confidence: 99%
“…Therefore, the water film cooling method is more effective in cooling the PV modules than rain imitation. The water spraying technique improved the solar energy generation performance because it has additional benefits and cooling, such as evaporation and cleaning of the surface of PV modules [66].…”
Section: Water Spraying Techniquementioning
confidence: 99%
“…A step further could be directed towards the optimization of the water spray cooling approach and to investigate the impact of the water temperature with respect to the performance response. An experimental setup with three nozzles at a spray angle of 90° was tested and discussed in work [52], Fig. 33.…”
Section: Direct Water Coolingmentioning
confidence: 99%
“…33. Tested cooling approach with three nozzles, [52] The double active water based cooling approach was proposed in work [53] where water spray was implemented over the front surface of a PV panel (20 Wp), while on the backside surface of the PV panel, direct water cooling was ensured. The configuration was tested in UAE (Sharjah) climate circumstances.…”
Section: Direct Water Coolingmentioning
confidence: 99%
“…The results showed that the electrical PV panel power increased by 15.5% (effective 10.0% for front cooling), 13.97% (effective 8.4% for back cooling), and 17.4% (effective 11.9% for both sides simultaneously), compared with the noncooled panel, and the temperature of the panel reduced from an average of 55°C (uncooled PV panel) to 27°C for the front, 32°C for the rear, and 24°C for simultaneous front and rear panel cooling. A low cost and high‐performance PV cooling system that can dramatically lower the operating temperature of a module was developed in the study reported by Benato and Stoppato 24 . This study collected experimental measurements that would help identify a PV cooling arrangement that would ensure the best compromise of water film uniformity, reduction of module temperature, minimization of water consumption, and maximization of module power generation.…”
Section: Introductionmentioning
confidence: 99%